Needs of Young African Neurosurgeons and Residents: A Cross-Sectional Study - Kanmounye, Ulrick S.; Robertson, Faith C.; Thango, Nqobile S.; Doe, Alvin Nah; Bankole, Nourou Dine Adeniran; Ginette, Pape Aicha; Ondoma, Solomon; Balogun, James A.; Opoku, Isabella; Jokonya, Luxwell; Mbaye, Thioub; Shabhay, Zarina A.; et al. (Frontiers in Surgery, 2021)
Introduction Africa has many untreated neurosurgical cases due to limited access to safe, affordable, and timely care. In this study, we surveyed young African neurosurgeons and trainees to identify challenges to training and practice. Methods African trainees and residents were surveyed online by the Young Neurosurgeons Forum from April 25th to November 30th, 2018. The survey link was distributed via social media platforms and through professional society mailing lists. Univariate and bivariate data analyses were run and a P-value <0.05 was considered to be statistically significant. Results 112 respondents from 20 countries participated in this study. 98 (87.5%) were male, 63 (56.3%) were from sub-Saharan Africa, and 52 (46.4%) were residents. 39 (34.8%) had regular journal club sessions at their hospital, 100 (89.3%) did not have access to cadaver dissection labs, and 62 (55.4%) had never attended a WFNS-endorsed conference. 67.0% of respondents reported limited research opportunities and 58.9% reported limited education opportunities. Lack of mentorship (P = 0.023, Phi = 0.26), lack of access to journals (P = 0.002, Phi = 0.332), and limited access to conferences (P = 0.019, Phi = 0.369) were associated with the country income category. Conclusion This survey identified barriers to education, research, and practice among African trainees and young neurosurgeons. The findings of this study should inform future initiatives aimed at reducing the barriers faced by this group.